Legal Enforcement for IUU Fishing in Indonesian Sovereignty And Jurisdiction: A Case Analysis of The Capture of Foreign Vessels by The Indonesian Government - ernawati, Ninin; Shafira, Maya; Achmad, Deni; Tarigan, Rehulina; Silviani, Ninne Zahara (Magister of Law, Faculty of Law, University of Mataram, 2022)
Illegal, Unregulated, and Unreported (IUU) Fishing cases often occur in Indonesia. This is due to the lack of supervision by the Indonesian government towards foreign vessels conducting fishing activities in Indonesia’s territorial waters, and exclusive economic zone (EEZ). IUU fishing has caused huge losses to the country. One of the perpetrators engaged in this illegal act was the Thai Silver Sea 2 ship. The ship entered Indonesian territorial waters specifically in Sabang waters, by flying the Indonesian flag to trick the Indonesian government patrolling around the area. However, gradually the Indonesian government became aware of the existence of foreign vessels which had been suspected by Indonesia for a long time because it often turned off VMS so that its existence could not be detected by the Indonesian government. This study delves deeper into whether the actions conducted by Silver Sea 2 Vessels violate Indonesian regulations and UNCLOS 1982. Additionally, it examines the compatibility of the Indonesian government’s legal enforcement of IUU Fishing with UNCLOS 1982. The results indicate that the actions of SS2 ships violated Indonesian legislation and UNCLOS 1982. Furthermore, the handling of this case by the Sabang District Court was deemed appropriate.